2019
DOI: 10.1002/slct.201803769
|View full text |Cite
|
Sign up to set email alerts
|

Ciprofloxacin‐Loaded Ceramic/Polymer Composite Coatings on Ti with Improved Antibacterial and Corrosion Resistance Properties for Orthopedic Applications

Abstract: Past few decades witnessed the upcoming of osteomyelitis which is a challenging infectious bone disease. Complications related to this infection is encountered by local drug delivery via orthopedic surgery. In this work, TiO 2 -SiO 2 based bioceramics coatings were fabricated on Ti alloy by anodization method using sulphuric acid and Sodium silicofluoride (SSF) as an electrolyte. Plasma polymerized ethylenediamine (PPEDA) thin film deposited on composites by inductively coupled plasma chemical vapor deposition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…For example, chitosan (CS) and gelatin (GE), deposited on PEO-treated CP-Ti by cross-linking to the UV light-induced polymer graft, produce a negligible increase in corrosion resistance compared with a stand-alone PEO coating, but improve the surface biocompatibility in regards to fibroblast cell adhesion and growth [406]. Similar results in terms of insignificant enhancement of corrosion resistance were obtained by Sasireka et al [407] who deposited plasma-polymerized ethylenediamine (PPEDA) onto anodized Ti-6Al-4V alloy, whereas Kazek-Kęsik et al even observed a slight increase of corrosion current density of Ti-Mo/PEO/PLGA hybrid system compared with stand-alone PEO-treated ones [327]. In the latter case this was related to the possibility of an experimental error due to the increase of the real surface area of the specimen during the degradation of a hybrid coating.…”
Section: Monolithic Polymer Top-coatssupporting
confidence: 55%
“…For example, chitosan (CS) and gelatin (GE), deposited on PEO-treated CP-Ti by cross-linking to the UV light-induced polymer graft, produce a negligible increase in corrosion resistance compared with a stand-alone PEO coating, but improve the surface biocompatibility in regards to fibroblast cell adhesion and growth [406]. Similar results in terms of insignificant enhancement of corrosion resistance were obtained by Sasireka et al [407] who deposited plasma-polymerized ethylenediamine (PPEDA) onto anodized Ti-6Al-4V alloy, whereas Kazek-Kęsik et al even observed a slight increase of corrosion current density of Ti-Mo/PEO/PLGA hybrid system compared with stand-alone PEO-treated ones [327]. In the latter case this was related to the possibility of an experimental error due to the increase of the real surface area of the specimen during the degradation of a hybrid coating.…”
Section: Monolithic Polymer Top-coatssupporting
confidence: 55%
“…With the aim of investigating the drug release profile of the prepared nHAp samples, firstly their drug loading efficacy was examined given that it impacts the release profile to a great extent. 87 The loading characteristics were evaluated in terms of entrapment efficacy (EE) and loading capacity (LC), as shown in Fig. 12a .…”
Section: Resultsmentioning
confidence: 99%
“…BF-PCL films revealed a burst release during the first hour of immersion followed by a further release of the remaining load up to ~90% in 96 h. However, for the loaded Mg-HHC system, a rather gradual elution was observed over the time, with only 20 and 40% of PAR and CIP loads released after 10 days, respectively. This may be associated with the formation of insoluble chelates between Mg 2+ and Ca 2+ and CIP 0 or PAR 0 (Zwitterionic) in the medium [34][35][36][37], reducing the PAR and CIP release. This is in agreement with the observation of other previous reports where the complexation of different cations with CIP and PAR structures has been shown to reduce bioavailability [38,39].…”
Section: Paracetamol and Ciprofloxacin Release From Bf Pcl Layermentioning
confidence: 99%